Growth hormone deficiency as a cause for short stature in Wiedemann–Steiner Syndrome. (23rd August 2018) - Stoyle, George; Banka, Siddharth; Langley, Claire; Jones, Elizabeth A; Banerjee, Indraneel
Summary: Wiedemann–Steiner Syndrome (WSS) is a rare condition characterised by short stature, hypertrichosis of the elbow, intellectual disability and characteristic facial dysmorphism due to heterozygous loss of function mutations in KMT2A, a gene encoding a histone 3 lysine 4 methyltransferase. Children with WSS are often short and until recently, it had been assumed that short stature is an intrinsic part of the syndrome. GHD has recently been reported as part of the phenotypic spectrum of WSS. We describe the case of an 8-year-old boy with a novel heterozygous variant in KMT2A and features consistent with a diagnosis of WSS who also had growth hormone deficiency (GHD). GHD was diagnosed on dynamic function testing for growth hormone (GH) secretion, low insulin-like growth factor I (IGF-I) levels and pituitary-specific MRI demonstrating anterior pituitary hypoplasia and an ectopic posterior pituitary. Treatment with GH improved height performance with growth trajectory being normalised to the parental height range. Our case highlights the need for GH testing in children with WSS and short stature as treatment with GH improves growth trajectory. Learning points: Growth hormone deficiency might be part of the phenotypic spectrum of Wiedemann–Steiner Syndrome (WSS). Investigation of pituitary function should be undertaken in children with WSS and short stature. A pituitary MR scan should be considered if there is biochemical evidence of growth hormone deficiency (GHD). Recombinant human growth hormone treatment should be considered for treatment of GHD.